(untitled) (Research, Society and Development, 2022)
Objective: To identify scientific production on pedagogical conceptions those underlie the pedagogical projects of nursing technical courses in Brazil. Methods: This is an integrative review of publications that address the pedagogical plan of nursing technical courses in the country, seeking to answer the question "What are the pedagogical conceptions that underpin the curricula of nursing technical courses in Brazil?" Results: A total of 679 articles were identified, six of which were included. All were qualitative, used distinct designs and were published in five journals in the area of Nursing. The data found in the primary studies included in this integrative review were synthesized in two categories: "The problematization in the pedagogical centrality of Technical Education" and "Curriculum by competencies for a training committed to professional practice of integral health care". It was observed a pedagogical direction towards the use of problematization and a tendency towards a curriculum by competencies, notably in public education. Conclusion: A mismatch was observed between what is described in the pedagogical project of the courses addressed and what is implemented by the respective professors.